PENGAYAAN BAHASA INDONESIA MELALUI ISTILAH BARU TERKAIT COVID-19 - Lapasau, Merry (Sunan Kalijaga State Islamic University Yogyakarta, 2020)
The present study aims to analyze new word formations in Indonesian related to COVID-19 and identify its function in online newspapers. This research uses a descriptive qualitative approach by adapting generative morphological theories as the framework. The research objects are 32 new word formations found in various texts in online newspapers in Indonesia collected between April 2020 to August 2020. The data were analyzed using the top-down technique distribution method. This method uses a determinant in the language element itself, namely the data selection technique based on specific categories in terms of grammarism in accordance with the natural characteristics of the research data. The study shows that the new word formation in modern Indonesian related to COVID-19 can be obtained by coining roots, compounding, abbreviation, and acronym. Those unique word formations are originated primarily from Indonesian and English. The function of its usage is mainly referential (abbreviation and acronym) and expressive (roots and compounding). We create new words to fulfill the designation needs of new issues that appear in society. Furthermore, the development in society, especially in coping with global health issues, has also contributed to the enrichment of Indonesian vocabulary.